Determinant of Tax Avoidance with Company Size as a Moderating Variable: Empirical Study in Indonesia - Andesto, Ronny; M, Roni Okto Junaedi (Baca Dulu Publisher, 2025)
This study aims to investigate and analyze the impact of environmental, social, and governance (ESG) performance, institutional ownership, and foreign ownership on tax avoidance practices. In addition, this study also examines how company size acts as a variable that moderates the relationship. Using a quantitative approach, this study uses data from 21 purposively selected publicly listed manufacturing companies during the 2019-2023 period. Panel data linear regression analysis and moderation regression analysis were used in data processing.The research findings show that ESG performance, institutional ownership, and foreign ownership have a significant influence on tax avoidance in listed manufacturing companies during the 2019-2023 period. Furthermore, this study reveals that firm size can strengthen the influence of ESG performance, institutional ownership, and foreign ownership on tax avoidance tendencies.